The emerging web 2.0 social media as a tool to develop engaged audiences for behaviour change in health promotion: an overview - AuYong, Hui-Nee (2017)
Sharing of health information which is related to health becomes easier with the introduction of new technologies such as Web 2.0 social media networks.Social media networks represent a rather innovative way of online information and knowledge repositories.On the other hand, many non communicable diseases are caused by unhealthy urban lifestyle.Hence, the practice of the healthy lifestyle behaviors should be promoted for sustainability.Besides, in order to cut down the chronic diseases, workplace is one of the key channels for the delivery of interventions among adult populations.Latest development in information and communication technologies (ICT) has given positive influences in health communication.The new technology is believed to be more engaged because it involves visual, audio and animation simultaneously, thus it is more reachable and collaborative.This paper reviews strategies to manage health promotion. Nevertheless, improvement is still needed to achieve successful health promotion.This paper also provides insights of issues and poses future topics of health promotion to consider.